Sustainability Practices in Startups: A Comparative Study Between Developed and Developing Economies - Siti Nuryanah; Sonya Kusuma Putri; Auliya Putri (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
This paper examines the adoption of sustainability practices in startups, comparing those in developed and developing economies. With a growing emphasis on sustainable development, startups play a crucial role in driving environmental and social change. The study analyzes the challenges and opportunities faced by startups in both contexts, focusing on resource management, green innovation, and social responsibility initiatives. The findings reveal distinct approaches between the two groups, with startups in developed economies leveraging more advanced technologies, while those in developing economies rely on cost-effective, local sustainability practices. Recommendations are provided for fostering sustainability in the startup ecosystem.